EDUCATION ON DIGITAL MARKETING FOR SMES IN MEDAL RAHAYU SUBDISTRICT OF AMBIT VILLAGE SUMEDANG-WEST JAVA - Faeni, Dewi Puspaningtyas (Journal of Sustainable Community Development (JSCD), 2024)
The purpose of this social responsibility services to convey the importance of financial management, product and operation management and most of all marketing management and how social media uses for the purpose of digital marketing by utilizing market place and such in the social media. This social responsibility services will assist Small Medium Enterprises (SMES) in resolving problems regarding environment and operation issues in correlation with planning, organizing, packaging and marketing via digital platforms. This social responsibility services are a community services involving 32 universities representatives which carried out their individual duties to perform and lecture best practices to the society in Ambit Village, Subdistrict of Sumedang West Java. These activities were conducted during 22nd and 23rd of December 2023 involving 150 local business ventures who were more than eager to develop their businesses to the next level. 150 local businesses were involving SMES operate in a variety of home industries, including handicrafts, eco-tourism, and food production. The result of this social responsibility services where participants were very satisfying and felt the insights and needs for such acts to develop skills, knowledge and ability among them. The evaluation revealed an increase in knowledge of digital marketing before and after the distribution.